On ecological dumping - Michael Rauscher (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
Ecological dumping is a catchword used in the public discussion on environmental policies in open economies to characterize situations in which a country uses a too-lax environmental legislation as an instrument of achieving trade-related economic policy goals. The paper first tries to define ecological dumping and then looks at economic motives underlying this kind of environmental policy. The approaches considered in this paper are the terms-of-trade argument, strategic trade policy and a public choice model in which the government either maximizes tax revenues or supports sector-specific interest groups.
Keywords: 330; Dumping; Umweltpolitik; Terms of Trade; Strategische Handelspolitik; Theorie